PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X OTOMASI 1 SMKN 1 BATAM - Fahmi, Ayu Rachma; ', Kartini; Heleni, Susda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve the learning process and increase the student?s mathematics learning outcomes through the implementation of Cooperative Learning Structural Approach Numbered Heads Together (NHT). This research is the Classroom Action Research with two cycle. The research was conducted in class X Automation 1 SMKN 1 Batam in the first semester of the 2016/2017 academic year with the subject of as many as 40 students, consist of 26 boys and 14 girls. The research instrument consists of learning devices and instrument data collectors.The instrument data collector used in this research is the observation sheet and math achievement test. Data analysis technique used is descriptive statistical analysis. Based on the result of the activity techer and students can be concluded that this research can improve the learning process and based on the result of the Minimum Criteria of Achievement can be concluded that this reserch can increase the student?s mathematic learning outcomes. Result ofthis research indicates that implementation of Cooperative Learning Structural Approach Numbered Heads Together (NHT) can improve learning process and increase mathematics learning outcomes from the students at class X Automation 1 SMKN 1 Batam in the first semester academic years 2016/2017 on main material systems of linear equations and inequalities.